Case Report: Management Penetrating Brain Injury Across Middle Third of Superior Sagittal Sinus - Chumaidi, Achmad; July, Julius (Medicinus, 2022)
Background: Penetrating cranial injuries are rarely reported on thick parietal bone. Goal of its management include removal of the foreign object while minimizing furher damage to the brain and associated neurovascular structures, also prevent further complications.Case Description: We report a case of a 22-year-old male presented with machete stucked in his head following an accidentally fell down of the weapon from a coconut tree. The cranial location affected were midparietal. He was disoriented on admission, with neither neurological focal signs nor seizure. Computed tomography (CT) revealed that the object penetrate middle superior sagittal sinus. After emergency craniotomy to remove the objects, debridement, dural sinus repair were performed. Recovery was complete without sequelae.Conclusion: Laceration of the middle thirds of the superior sagittal sinus require special handling and care during surgery. Operative approach and treatment strategies are among the most important considerations to achieve the best patient outcomes.